Tracing and Exploring Similar Mentions with Various Meanings in Ancient Languages - Bintang Caesario Perdana (FKIP - Universitas Pahlawan Tuanku Tambusai, 2024)
Research Similar references whose meanings differ in ancient languages are an interesting linguistic phenomenon to be examined. In this article, the author explores how words with different meanings were found in the Air Tiris Kampar area in ancient languages. An interesting example is the word